Evaluation and risk factors of arterial stiffness in patients given peritoneal dialysis - SU Xiao-yan; DING Su; ZHENG Wei-ping; ZOU Yuan-fang; LI Ai-ting; DENG Hui-zhao; HUANG Hui (Linchuang shenzangbing zazhi)
Objective To evaluate and analyze risk factors of arterial stiffness in patients given peritoneal dialysis.Methods A total of 86 patients with end-stage kidney disease undergoing peritoneal dialysis,19-60 years old,without diabetes mellitus were enrolled.Baseline characteristics,brachial-ankle pulse wave velocity（baPWV） and other laboratory measurements were collected and analyzed.BaPWV was determined using an automated,non-invasive,waveform analysis device.Results According to baPWV,the patients were divided into high baPWV group（baPWV>1 400 cm/s,n =39） and normal baPWV group（baPWV<1 400 cm/s,n = 47）.As compared with CAPD patients with normal levels of baPWV,the CAPD patients with high levels of baPWV had significantly higher baPWV[（1 961 ±412） cm/s vs.（1 349 + 234） cm/s,P<0.01],longer dialysis duration,higher ischemia modified albumin[IMA,（95.8 ± 6.0） kU/L],and higher sensitivity C-reactive protein[hsCRP,（5.1±1.0）mg/L].In addition,the high baPWV CAPD patients also had a lower level of total urea clearance index（Kt/V,1.8±0.9）,total creatinine clearance[（56.5±11.4）L·W-1·（1.73m2）-1],residual GFR[rGFR,（3.8±1.0）L·W-1·（1.73 m2）-1],and serum albumin[（31.6±5.3）g/L].The correlation analysis showed that baPWV was significantly correlated with dialysis duration,serum calcium,IMA and hs-CRP,and negatively with total Kt/V,rGFR and serum albumin（P<0.05）.Logistic regression analysis revealed that dialysis duration,rGFR and hs-CRP were the most significant factors affecting baPWV in PD patients.Conclusions Arterial stiffness,assessed by baPWV,had an independent correlation with dialysis duration,residual renal function,microinflammation in young and middle-aged non-diabetic patients undergoing peritoneal dialysis.To protect the residual renal function,improve the inflammatory state,and improve the adequacy of peritoneal dialysis can reduce the risk of atherosclerosis in patients with peritoneal dialysis,and reduce the incidence of cardiovascular events.